The Plurality of Goal-setting in Pedagogical Activity: Integration of Mathematics on a Chessboard - S. N. Dvoryatkina; V. S. Karapetyan; S. A. Rozanova (Высшее образование в России)
The article reveals the potential for the integration of mathematics education and gaming activities in the formation of professional competencies of a future teacher. The disclosure of a wider range of possibilities for the interdisciplinary integration of mathematical knowledge and chess skills in the context of setting and selecting goals for solving mathematical problems on a chessboard seems to be very relevant for teaching students. A modern professional is constantly faced with the need to change and select goals, search for the optimal way out in conditions of pedagogical uncertainty and pedagogical risk. An important condition for its self-realization in pedagogical activity is goal-setting. Goal-setting as a choice or resolution of uncertainty in a plurality of alternatives involves understanding by learners of their own existential essence with subsequent creative actions. Knowledge of the mechanisms of goal-setting is necessary both for assessing by a teacher his/her own activities (level of universal competencies – critical thinking, self-organization and selfdevelopment), and the activities of students (level of general professional competencies – monitoring and evaluation of educational results). Therefore, the authors propose to study the features of goal-setting with a plurality of alternatives during the process of training bachelors and masters majoring in pedagogy within the disciplines of the methodical module. The goal of the article is to theoretically substantiate, develop and implement the technology of integrative teaching mathematics on the basis of chess game with the actualization of the phenomenon of a plurality of goal-setting as an effective mechanism of content modernization in training programs of future math teachers. The main result of the research we consider the developed integrative technology of teaching mathematics on the basis of solving problems on a chessboard with the actualization of the phenomenon of goal setting plurality. To implement the technology, a holistic, hierarchical complex of multi-stage math problems on the chessboard has been composed, which encourages students to master not only various methods (combinatorial, probabilistic, graph and set theory, mathematical and computer modeling), but also to develop the basic qualities of personality, such as creativity, reflection of one’s own choice, creative independence, motivation. The materials of the article are of scientific and practical value for researches in the field of math teaching methods, psychology, and pedagogy and accounting for them in the adjustment of programs and curricula in pedagogical universities.